Implementasi Perda Nomor 4 Tahun 2010 tentang Pengelolaan Sampah untuk Mewujudkan Lingkungan yang Bersih dan Sehat - Nurohman, Maman (Uniku Law Review, 2023)
Good waste management is very necessary for good waste management to maintain a clean environment. According to Law no. 18 of 2008, the Government and regional governments are tasked with ensuring that good and environmentally sound waste management is implemented in accordance with the objectives of this Law. In the Kuningan Regency environment, waste management policies are supported by the Kuningan Regency Regional Regulation Number 4 of 2010 concerning Waste Management. Even though there is a regional regulation that regulates, problems regarding waste management still occur. One of the waste problems in Mancagar Village, Garawangi District, Kuningan Regency is that people throw rubbish into the river, causing environmental pollution. This is a lack of awareness among the local community regarding waste management. The research method used is an empirical juridical research method by examining the applicable legal provisions and what is happening in reality in the field with the aim and purpose of knowing and finding the facts and data needed, after the required data is collected then it goes to identifying the problem at hand. finally leading to solving the problem. Regarding the obstacles that occur in the Mancagar Village community, the Village Government already has strategies and steps to be taken in the future, but before this the Government must first increase awareness of the local community.